Efficacy of the Radiotherapy on Darier's Disease: An Indirect Evidence - Ala Podgornii; Patrizia Ciammella; Dafne Ramundo; Cinzia Iotti (Hindawi Limited, 2013)
Darier's disease (DD) is an autosomal dominant dermatosis characterized by hyperkeratotic papules that are mainly located in the seborrheic areas and pushups, handheld wells, and nails. The disease often appears at a young age, typically by the third decade, with no sex predilection. There is currently no standard therapy and there are usually topical palliative therapies. We present the case of an affected 42-year-old woman treated with radiation therapy for early breast cancer. Before the radiotherapy, the patient showed hyperkeratotic, brownish papules extending in a linear pattern for the neck to the abdomen, especially on both breasts and inframammary area. During the radiation, she developed grade 1 to 2 dermatitis in the irradiated area. At a followup of 6 months, the patient has no skin lesions in the irradiated zone. This report suggests that the radiotherapy is not contraindicated and may indeed be effective in local control of skin lesions in DD.